Soil erosion thresholds and alternative states in northeastern Patagonian rangelands - Chartier, Marcelo Pablo (2006)
In semiarid rangelands, continuous grazing may decrease vegetation cover, accelerating soil erosion and eventually causing a transition to an alternative, degraded state. State-and-transition models invoke process-based explanations of alternative states, but there are few examples that use empirical data on key factors and processes. We used rainfall simulation to determine 1) the relationships between soil surface characteristics and interrill erosion in 3 spatially related plant communities: stable grass with scattered shrubs (GS), degraded grass with scattered shrubs (PGS), and degraded shrub steppes (DSS), and 2) the site conservation threshold (SCT) of this rangeland. We also analyzed the effect of past erosion on soil and vegetation characteristics. In the GS, sediment production and sediment concentration were significantly lower (p < 0.05) than in the DGS and the DSS. The main soil protection factors in the GS and in the DGS were perennial grass and litter cover, while in the DSS, gravel cover became the main soil protection factor. The SCT, the point at which the rate of soil erosion increases markedly, corresponded to a plant-and-litter cover close to 90% and occurred within the DGS. Although this plant community may reverse back to the conserved GS, long-term accelerated erosion may result in enough soil loss to trigger irreversible changes and prompt the transition to the DSS. The threshold underlying this transition would be reached when the A horizon is severely reduced by erosion. Under these conditions, the soil hydrological properties are affected irreversibly, preventing perennial grass establishment. While the GS represents a resource conserving plant community, desirable for both forage production and soil protection, the DSS represents a dysfunctional state with a minimum forage value. The DGS represents an unstable and transitional community that, without management intervention to halt soil erosion, will likely change into the DSS.